3(-u-5)+8(2u+1)=0

Simple and best practice solution for 3(-u-5)+8(2u+1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-u-5)+8(2u+1)=0 equation:


Simplifying
3(-1u + -5) + 8(2u + 1) = 0

Reorder the terms:
3(-5 + -1u) + 8(2u + 1) = 0
(-5 * 3 + -1u * 3) + 8(2u + 1) = 0
(-15 + -3u) + 8(2u + 1) = 0

Reorder the terms:
-15 + -3u + 8(1 + 2u) = 0
-15 + -3u + (1 * 8 + 2u * 8) = 0
-15 + -3u + (8 + 16u) = 0

Reorder the terms:
-15 + 8 + -3u + 16u = 0

Combine like terms: -15 + 8 = -7
-7 + -3u + 16u = 0

Combine like terms: -3u + 16u = 13u
-7 + 13u = 0

Solving
-7 + 13u = 0

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + 13u = 0 + 7

Combine like terms: -7 + 7 = 0
0 + 13u = 0 + 7
13u = 0 + 7

Combine like terms: 0 + 7 = 7
13u = 7

Divide each side by '13'.
u = 0.5384615385

Simplifying
u = 0.5384615385

See similar equations:

| 7r-5-6=4(r+1)+3(2r+1) | | 6x-8=8x-3x | | 9(x+18)+12=8(x+8)+10 | | 2x+1=2x+3 | | 2d+10=6-10 | | 3x+3(2x-1)=4x+-7 | | -4(3u-1)+7(3-2u)=0 | | -6(x+4)=-6(x+1) | | x^2+5-36=0 | | 3d+d-7=6.3 | | -4x-5(-x+10)=-43 | | 4x+7-3(x-4)=-26 | | 2x+136-136=180-136 | | x-0.2x=0 | | 4x+3x=6x+9 | | 7-16a=-3(4a-13) | | 3(-7b+5)=-7(3b+5) | | k=8k+38 | | 9-3(-4+3x)+12x=0 | | 4x+11=x^2-10 | | y=x^8-5x^4+4 | | 1-6x=2x+17 | | -4(-2x-7)+6x-7=0 | | 4(1+2m)=3(-4-m)+5 | | (y+2)/4=5 | | -3(a+2)+9=-12 | | (5n-4)(5n+4)=-61 | | 8+9x+4(11-2x)=0 | | 4x^4-324=0 | | (5x-6x^3+2x^4)-(9x^3+4x^4-7)= | | -2p-2(3-4p)=2(p-2)-30 | | -6+3(6-8n)=6(-7n-4) |

Equations solver categories